The relationship between home ownership and fall-related outcomes: The National Health and Aging Trends Study. - Ching-Yao Tsai; Tao-Hsin Tung; Yang-Tzu Li; Wei-Cheng Chen (Public Library of Science (PLoS), 2021)
Although many studies have tried to explore the association between fall incidents and fear of falling (FOF)/worry about fall-limited activities and various risk factors, few studies have recognized the relationship between house ownership and fall-related outcomes. The aim of this study was to assess whether house ownership will affect an older adult's experience of falling or lead to fear of falling. The National Health and Aging Trends Study (NHATS) collected data that would provide an understanding of basic trends in people aged 65 years and older living in the United States of America. This study conducted round one of the NHATS and did logistic regression to examine the relationship between house ownership and fall-related outcomes among 7,090 persons aged 65 or older. Twenty five percent of the sampled population who lacked house ownership. All fall-related outcomes (fall last month, fall last year, fear of falling, and worry about fall-limited activities) were statistically significant in the bivariate analysis. Multiple logistic regression analysis showed that house ownership (OR = 0.75, 95%CI: 0.65-0.86) was significantly associated with fear of falling after adjusting for other covariates. The findings underscore the association between the lack of house ownership and fall-related outcomes.